Fiskalföderalismus in Deutschland – Was zu tun ist - Nadine Riedel; Martin Simmler (Wirtschaftsdienst, 2024)
There is a need for some reform in the fiscal federal system in Germany. On the expenditure side, the relationship between administrative and legislative competences needs to be clarified. An orientation toward real values is recommended in the financial equalisation system ("Finanzausgleich"). In addition, the so-called population refinement ("Einwohnerveredelung") should be reconsidered. We advocate greater tax autonomy for the federal states. A surcharge on income tax would be a good option here; the real estate transfer tax ("Grunderwerbsteuer"), on the other hand, is problematic as it is an autonomous tax instrument of the states. At the local level, we show that the trade tax ("Gewerbesteuer") is accompanied by considerable economic distortions and we advocate for its abolition. The property tax ("Grundsteuer"), on the other hand, is well-suited as an autonomous local tax, and updating the outdated standard values offers an opportunity to enhance its effectiveness in local contexts.
Keywords: H30; H77; H21; H70; 330